Representation of Toxic Masculinity In Extrajoss Advertisements: A Multimodal Analysis - Prayogi, Khoirunnisa Andrevi (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
This study examines how toxic masculinity is represented in Extra Joss advertisements on Instagram, particularly those featuring the tagline “Laki Buktikan.” It explores how visual and textual elements construct and reinforce harmful masculine ideals in Indonesian media. Using Terry A. Kupers’ (2005) framework, the analysis focuses on traits such as homophobia, greed, and violent domination. Kress and van Leeuwen’s (2006) visual grammar framework is also applied to assess meaning-making through representational, interactive, and compositional metafunctions. Employing a qualitative approach with Multimodal Critical Discourse Analysis (MCDA), the study analyzes twelve selected Instagram advertisements. The findings reveal that Extra Joss ads frequently promote toxic masculine traits through aggressive postures, stoic expressions, and action-oriented slogans. These elements normalize emotional suppression, dominance, and relentless performance as desirable male characteristics. The study concludes that the advertisements contribute to the construction and normalization of toxic masculinity by combining verbal and visual strategies to promote a narrow and rigid masculine identity.